Potensi Wisata Di Kecamatan Dusun Selatan Kabupaten Barito Selatan - Noor Hamidah; Mahdi Santoso; Noor Mahmudah (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2023)
South Barito Regency is located in Central Kalimantan Province which has potential in the tourism sector. One of the districts as a tourist attraction in South Barito Regency is Dusun Selatan District. Tourist attractions include natural attractions, sports attractions, man-made attractions and special interest attractions. There are twenty one tourist objects in Dusun Selatan District, with developing tourist areas namely natural tourism, man-made tourism and cultural tourism. The aim of the research is to identify the tourism development potential of Dusun Selatan District, South Barito Regency from various natural resources, cultural tourism and artificial tourism. The tourism potential in several villages in Dusun Selatan District is an opportunity for the development of a tourist area in South Barito Regency. The research method uses qualitative methods based on data from literature studies and observations, to process the analysis and synthesis of tourism potential with reference to regional analysis through the SWOT analysis tool. The results of the research include: location analysis, existing potential analysis, and tourism development analysis